Musical Works & Performances: A Philosophical Exploration - Davies, Stephen (Oxford Clarendon Press, 2001)
What are musical works? Are they discovered or created? Can recordings substitute faithfully for live performances? This book considers these and other intriguing questions. It first outlines the nature of musical works, their relation to performances, and their notational specification; it then considers authenticity in performance, musical traditions, and recordings. Comprehensive and original, the volume discusses many kinds of music, applying its conclusions to issues as diverse as the authentic performance movement, the cultural integrity of ethnic music, and the implications of the dominance of recorded over live music.
Keywords: Music philosophy and esthetics; Performance